DEVELOPMENT AND CHARACTERIZATION OF SILDENAFIL CITRATE ORAL THIN FILMS (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The current work aimed to develop sildenafil citrate (SC) oral thin films. SC oral thin films (OTF) were prepared by solvent casting method. The ingredients include hydroxypropyl methylcellulose (HPMC), E4 (as film former), glycerol (as lubricating agent), polyethylene glycol 600 (as plasticizer), rose oil (as flavoring agent), and de-ionized water (as solvent). The SC-OTFs were successfully prepared by the solvent casting method. The drug excipient compatibility studies showed the absence of drug excipient interactions in fourier transform infrared spectroscopy (FTIR) spectra. All the prepared formulations (F1 to F6) were evaluated for several physicochemical parameters like morphology (i.e., size, shape, color), thickness, uniformity (i.e., content and weight), surface pH measurement, in vitro disintegration time, in vivo studies (i.e., taste), tensile strength, folding endurance and in vitro drug release and all were found within pharmacopoeial limits. In vitro, drug release studies (F1 to F6) in simulated salivary fluid (6.8 pH phosphate buffer) showed that 98 ± 1.26% drug was released from F4 in 60 sec. The OTF is a promising formulation for SC that results in high solubility, rapid onset of action, and enhanced systemic bioavailability (BA).